Potential tumor marker for hepatocellular carcinoma identification: PI3K and pro-inflammatory cytokines (TGF-β, IL-1, and IL-6) - Tabakhiyan, Fahimeh; Mir, Amirabbas; Vahedian, Vahid [UNESP] (De Gruyter, 2022)
Hepatocellular carcinoma (HCC), the most common form of liver cancer, is a leading cause of tumor-associated mortality worldwide. Diagnosis based upon non-invasive criteria is currently challenged by the need for molecular information that requires tissue or liquid biopsies. The progression of HCC is often associated with chronic inflammation, expression levels of inflammatory mediators, chemokine, and cytokines. In this study, we try to evaluate the PI3K and pro-inflammatory cytokines, TGF-β, IL-1, and IL-6 expression level in patients with liver cancer. The kupffer cells were isolated from patient's specimens. Real-time PCR was applied to evaluate the expression level of PI3K in cell lines or tumors. The concentrations of TGF-β, IL-1, and IL-6 were measured by the quantitative ELISA kit. PI3K mRNA expression in cancer cells was increased markedly vs. normal cells. The ELISA results demonstrated over expression of TGF-β, IL-1, and IL-6 in patients and positive correlation between tumor size and stage. This study suggests that targeting the expression level of PI3K and pro-inflammatory chemokine and cytokines, TGF-β, IL-1, and IL-6, may be a potential diagnostic strategy in HCC patients.
Keywords: hepatocellular carcinoma (HCC); inflammation; liver cancer; pro-inflammatory chemokine